EVALUASI PENGELOLAAN LIMBAH MEDIS PELAYANAN KESEHATAN GIGI PADA RUMAH SAKIT GIGI DAN KLINIK GIGI DITINJAU DARI ASPEK SISTEM MANAJEMEN: A SYSTEMATIC REVIEW - Herajeng Styamita Pradani; Sarto Sarto; Wiranto Wiranto (Berita Kedokteran Masyarakat (BKM), 2020)
AbstractBackground: Dentistry is growing rapidly around the world. There is an increasing number of dental health service facilities across the country. The quality of dental health and patient care has improved, but on the other hand, it has produced a large amount of medical waste. The amount of medical waste poses potential health risks and damage to the environment, if doesn't managed properly. Objective: To evaluate the management of medical waste in dental hospitals and dental clinics in terms of management aspects (input, process, output). Methods: This study was done with a systematic review method. Results and Discussion: The result of research data found 348 articles then filtered according to the research criteria so that 25 articles were obtained. The input category for medical waste management in dental hospitals was lack in terms of training for waste management officers and the foundation of infrastructures, especially personal protective equipments. The process category in dental hospitals, namely medical waste, has not all been disaggregated and the storage time exceeded the standard. The output category in dental hospitals showed that not all dental hospitals did the separation according to the category and there was no data on waste reduction. The input category for medical waste management in dental clinics was lack in terms of training, infrastructure advices, POSs and funding. Process categories in dental clinics were not up to standard including reduction, sorting, storage and transportation of medical waste. The output category in the dental clinics showed not all did the separation according to the category and there was no waste reduction. Conclusion: Dental hospitals and dental clinics have not fully implemented the recommendations of WHO (2014) and Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number 56 of 2015 regarding medical waste management.Keywords: dental waste management, dental hospital, dental clinic. AbstrakLatar Belakang : Kedokteran gigi semakin berkembang pesat diseluruh dunia. Terdapat peningkatan jumlah fasilitas pelayanan kesehatan gigi di seluruh negara. Kualitas kesehatan gigi dan perawatan pasien meningkat namun disisi lain menghasilkan limbah perawatan dalam jumlah besar. Besarnya limbah medis berpotensi menimbulkan dampak kesehatan dan mencemari lingkungan jika tidak dikelola dengan baik. Tujuan : Mengevaluasi pengelolaan limbah medis pada rumah sakit gigi dan klinik gigi ditinjau dari aspek manajemen (input, proses, output). Metode : Penelitian ini menggunakan metode systematic review. Hasil dan Pembahasan : Hasil pencarian data menemukan 348 artikel yang kemudian dilakukan penyaringan sesuai kriteria penelitian sehingga didapatkan  25 artikel. Kategori input dalam pengelolaan limbah medis di rumah sakit gigi terdapat kekurangan dalam hal pelatihan bagi petugas pengelola limbah dan pengadaan sarana prasarana terutama alat pelindung diri (APD). Kategori proses di rumah sakit gigi yaitu limbah medis belum semuanya terpilah sesuai jenisnya dan waktu penyimpanan limbah yang melebihi standar. Kategori output di rumah sakit gigi yaitu belum semua rumah sakit melakukan pemilahan limbah medis sesuai jenisnya dan belum terdapat data penurunan limbah. Kategori input dalam pengelolaan limbah medis di klinik gigi terdapat kekurangan dalam hal pelatihan, saran prasarana, POS dan pembiayaan. Kategori proses di klinik gigi yaitu pengurangan, pemilahan, penyimpanan dan pengangkutan limbah medis yang belum sesuai standar. Kategori output di klinik gigi yaitu belum semua klinik gigi melakukan pemilahan limbah medis sesuai jenisnya dan belum ada penurunan limbah. Kesimpulan : Rumah sakit gigi dan klinik gigi belum sepenuhnya melaksanakan rekomendasi dari WHO (2014) dan Peraturan Menteri Lingkungan Hidup dan Kehutannan nomor 56 tahun 2015 mengenai pengelolaan limbah medis.Keywords : pengelolaan limbah gigi, rumah sakit gigi, klinik gigi.